Theoretical aspects of the technical level estimation of electrical engineering complexes - S. V. Kolesnichenko; O. V. Afanas'eva (Записки Горного института, 2018)
The results of the analysis of methods allowing to evaluate the technical level of the electro technical complex (ETC) are presented and an original technique based on the application of the integral indicator is presented. The characteristic of each stage of the technique is given. The proposed scientific and methodological apparatus for assessing the technical level of the ETС is illustrated by the examples of the executive elements of the ETC comparison (internal combustion engines) using an integral quality index that links both the main characteristics of the samples and the means spent for achieving them. The proposed approach for assessing the technical level and quality of the ETC on the basis of an integral indicator should be carried out already at early stages of the life cycle when solving the following problems: the rationale for the economic feasibility of developing new or improving the quality of the produced ETCs; choice of the best option for the developed ETC; justification of requirements for the ETC; decision-making on the establishment and removal of ETC from production; substantiation of the rules of operation of the ETC in various conditions.